2016
DOI: 10.1080/21645515.2016.1139254
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of an engineered, yeast-expressedLeishmania donovaninucleoside hydrolase with immunogenic properties

Abstract: Leishmania donovani is the major cause of visceral leishmaniasis (kala-azar), now recognized as the parasitic disease with the highest level of mortality second only to malaria. No human vaccine is currently available. A 36 kDa L. donovani nucleoside hydrolase (LdNH36) surface protein has been previously identified as a potential vaccine candidate antigen. Here we present data on the expression of LdNH36 in Pichia pastoris and its purification at the 20 L scale to establish suitability for future pilot scale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…NHs have been considered as attractive drug targets in these organisms, taking into account their central role in the purine salvage pathway while many of these parasitic protozoa lack a de novo purine biosynthesis pathway . More recently, it was also proposed that vaccine development against NHs would prevent the replication of several pathogens during their early stages of life . Interestingly, in many other organisms NHs are present in parallel to a de novo purine biosynthetic pathway and nucleoside phosphorylases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NHs have been considered as attractive drug targets in these organisms, taking into account their central role in the purine salvage pathway while many of these parasitic protozoa lack a de novo purine biosynthesis pathway . More recently, it was also proposed that vaccine development against NHs would prevent the replication of several pathogens during their early stages of life . Interestingly, in many other organisms NHs are present in parallel to a de novo purine biosynthetic pathway and nucleoside phosphorylases.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] More recently, it was also proposed that vaccine development against NHs would prevent the replication of several pathogens during their early stages of life. 22,23 Interestingly, in many other organisms NHs are present in parallel to a de novo purine biosynthetic pathway and nucleoside phosphorylases. Often in these organisms the specificity constants (k cat /K M ) of the NHs for the canonical nucleosides are substantially lower compared to the NHs of protozoa.…”
Section: Introductionmentioning
confidence: 99%
“…With 79% of high overall recovery, we expect to collect approximately 785 mg of purified PpSP15 per litter of FS. When comparing with the purification process for several other reported recombinant protein vaccine antigens at similar fermentation scale, 24,27,[29][30][31][32] one can find that the process for PpSP15 requires much less volume of resins; in addition, size exclusion chromatography, a process not ideal for large-scale production, had been included in the purification process for some of these recombinant protein vaccine antigens to increase their purity. 24,27,30,31 However, the current purification scheme for PpSP15 does not require an size exclusion chromatography step to improve the purity to >95%, and all the chosen purification steps are scalable, except that dialysis was used to exchange PpSP15 into an appropriate buffer due to the small volumes at this development phase.…”
Section: Structure Assessment Using Circular Dichroismmentioning
confidence: 99%
“…22 In collaboration with the National Institutes of Health and the Uniformed Services University of the Health Sciences, we are now developing a leishmaniasis vaccine consisting of the sandfly antigen, PpSP15, and a well-characterized Leishmania parasite antigen, LdNH36. 24,25 Although the immunogenicity and efficacy studies of PpSP15 are ongoing, in parallel, we have been developing a scalable production process for this protein, thus allowing its rapid advancement to the clinic. During molecular cloning, the Escherichia coli expression platform was first explored since a protein homolog with close to 70% sequence similarity, PdSP15, from Phlebotomus duboscqi, had already been expressed in E. coli and then crystallized.…”
Section: Introductionmentioning
confidence: 99%
“…An E. coli-expressed L. donovani nucleoside hydrolase (LdNH36) surface protein has provided partial protection against L. donovani infection in mice (33). Expression of LdNH36 in P. pastoris produced LdNH36-Y-WT that was of significantly higher molecular weight than the E. coli expressed protein (34). Gel analyses suggested that expression in yeast resulted in several high-mannose glycoforms, whose presence was first reduced by mutating N-linked glycosylation sites located outside the major immunogenic domain from asparagines to serines (LdNH36-dg) and then removed by mutating asparagines to glutamines.…”
Section: Purified Recombinant Proteinsmentioning
confidence: 99%